SELLING DEMOCRACY ABROAD: SPANISH COMMITMENT IN 1988 CHILEAN PLEBISCITE - García Gutiérrez, Cristina (Revista de Historia Social y de las Mentalidades, 2024)
In 1988, Chile was preparing for a crucial  moment for his political future. According  to the schedule set by the 1980 Constitution,  there should be a plebiscite to decide how to  design the transition to a democratic system.  The options were a path led by Augusto  Pinochet by voting 'yes', or the opportunity  to hold free elections through the option  of "no". The opposition to the dictatorship  went through the observation of other  political experiences with similarities to the  Chilean case. The Spanish political transition  model appeared as a suitable example for  Chile. Meanwhile, from Spain, the socialist  government led by Felipe González and with  the support of other Spanish political parties,  got involved in the Chilean plebiscite, as  international observers, due to protect and  follow the political process. The Spanish  society, as well, did not feel apart from the  Chilean historical moment. By combining  different documentary sources, this article  shows the nature of this relationship which  brought together the two political contexts and  explains the Spanish interest in the Chilean  plebiscite.
Keywords: Chile; Spain; Transition; Plebiscite